Cannabis trademarks from the perspective of the Lanham Act and the European Union Trademark Regulation - Toms, Lintiņš (Riga Graduate School of Law, 2020)
This master’s thesis establishes superior applicability of the European Union Trademark Regulation with regard to recreational cannabis trademark registration in a federal state or federal union of states. Firstly, the author considers the Lanham Act of 1946 of the United States of America, as the basis for assessing the nation’s federal realm of trademark obtention, and the applicability of the statute in the context of those U.S. states where recreational cannabis use and sale has been legalised, and businesses operating therein. The author also considers individual U.S. state trademark laws as alternatives for securing trademark registrations with respect to state-legal recreational cannabis. Secondly, the author hypothetically introduces recreational cannabis legalisation in the European Union, and evaluates the applicability of European Union Trademark Regulation, as well as trademark laws of the member states of the European Union, in certain presumptive scenarios. Subsequently, the author juxtaposes findings with respect to both territories and draws conclusions on comparative effectiveness of each trademark system.
Keywords: Trade mark protection